Extensification to Increase the Number of Personal Tax Payer in Tax Office Pratama Cirebon - Sugiyarsih, Susi; Larasati, Endang; Suwitri, Sri; Ngatno, Ngatno (Budapest International Research and Critics University, 2021)
A source of income tax in Indonesia, therefore, the role of taxation is very important. It gives great role of taxes in development of country, demanding the government to maximize tax income. In order to increase the amount of income from the tax sector, The Directorate General of Taxes has agreed to the rules regarding the implementation of extensification and intensification taxes. Extensification section should be able to establish good cooperation with government and private agencies. This research was conducted at Tax Office Primary Cirebon, West Java, Indonesia. This study aims to provide an overview of extensification activities which is a proactive effort of Kantor Pelayanan Pajak (KPP) Pratama Cirebon in capturing taxpayers. As a result, extensification has a significant role in recruiting a personal taxpayer. The target in 2014 as many as 5 candidate taxpayers, 12 new taxpayers, and 47 registered taxpayers. The realization always exceeded the set target. As well as an improvement in the number of registered taxpayers. Significant improvement occurred in 2014. In earlier 2013, the number of registered taxpayers reached 198.916, an improvement in 2014 reached 226.947. Incoming 2015, the president instructed to push the income from the taxation sector and until June (second quarter) in 2015 reached 240.480. This paper describes how the role of extensification increase the number of personal taxpayer through proactive efforts in increasing state revenues from taxes coordinated by the Extensification section in Tax Office.